COATING COMPOSITIONS BASED ON ALDIMINES AND POLYISOCYANATES CONTAINING ALLOPHANATE GROUPS - HUNTER, JOHN H; HICKS, SHARON D; WICKS, DOUGLAS A (1995)
The present invention is directed to coating compositions which have long pot lives, may be rapidly cured under ambient conditions to provide coatings with improved optical properties and contain as binder a) a polyisocyanate component containing i) 5 to 100 % by weight of a monoallophanate and ii) 0 to 95% by weight of another polyisocyanate adduct, and b) an aldimine based on the reaction product of a polyamine having 2 or more primary amino groups with an aldehyde corresponding to the formula: O=CHCH(R1)(R2) wherein R1 and R2 may be the same or different and represent optionally substituted hydrocarbon radicals, or R1 and R2 together with the .beta.-carbon atom form a cycloaliphatic or heterocyclic ring, wherein components a) and b) are present in an amount sufficient to provide an equivalent ratio of isocyanate groups to aldimine groups of 0.5:1 to 20:1.